El laberinto, motivo sacramental en Tirso y Calderón - Oteiza, Blanca; Escudero Baztán, Juan M. (2013)
Este trabajo estudia el motivo del laberinto en dos autos sacramentales del siglo XVII: El laberinto de Creta de Tirso de Molina y El laberinto del mundo de Calderón de la Barca. Se enmarca dentro de un estudio más ambicioso que pretende abarcar la utilización del concepto de laberinto en el teatro del siglo XVII. La lectura de ambos textos muestra profundas transformaciones en el diseño, la estructura, la métrica y la utilización de la alegoría. El estudio comparado arroja una mayor destreza dramática en Calderón, frente a una acusada tendencia a la disgregación estructural en Tirso.
The present article analyses the motive of the labyrinth in two autos sacramentales of the 17th century: El laberinto de Creta by Tirso de Molina and El laberinto del mundo by Calderón de la Barca. It is conceived within the framework of a more amplified study with the aim of uncovering the use of the labyrinth as a nuclear concept of 17th century theatre. A lecture of both texts reveals profound transformations with respect to the allegory’s design, structure, metrics, and usage. The comparative study sheds light on a more skillful dramatization by Calderón, whereas in Tirso a structural decomposition is evident.
Keywords: Calderón de la Barca, Pedro, -- 1600-1681; Molina, Tirso de, -- 1579-1648; Crítica textual